PERFORMANCE ANALYSIS OF BIO-BRIQUETTING MACHINE WITH SCREW EXTRUDER TYPE BASED ON QUALITY OF BIO-BRIQUETTES - Puspa, Dilia; Yerizam, Muhammad; Zamheri, Ahmad; Wardhana, Agum Try (Politeknik Negeri Sriwijaya, Indonesia, 2023)
he purpose of this study is to design a bio-briquetting machine with screw extruder type to convert biomass into higher density based on quality standard of charcoal briquette SNI 01-6235-2000 and SNI 19-4791-1998. The machine had production capacity of 30 kg/hour, equipped with the motor of 1 HP which transmitted to the machine through pulley and belt, and also has cutter which rotates continuously. The raw materials of the bio-briquette were using bagasse and coconut shells. There are 6 parameters that are used to test the quality of bio-briquette such as calorific value, inherent moisture, ash content, dependability pressure, volatile matter content, and fixed carbon content. The bio-briquette was made from the raw materials using amylum adhesives with ratio 30:70:30. With feed as 5 kg, the machine produced 50 pieces of bio-briquette. The machine could produce good bio-briquettes such as calorific value of 6,511.3 cal/g, inherent moisture of 1.97%, ash content of 5.88%, volatile matter of 27.71%, fixed carbon content of 64.99% and compressive strength was 16.98 kg/cm2.